PENEROBOSAN HUKUM TERHADAP KETENTUAN PERKAWINAN BEDA AGAMA DI INDONESIA - NIM. A1012191008, BERLIAN SEPTIANA MIRINDA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac Marriage is a religious matter in which a relationship between two human beings, namely men and women who have grown up, has the desire to unite and promise in a sacred bond as husband and wife to form a happy family and multiply offspring. There is a meeting between the values shared by the community. One of the impacts of cross-cultural encounters causing a marriage, one of which is inter-religious marriage. Given that Indonesian society consists of various ethnicities, tribes and religions, interfaith marriage is nothing new. Even though it has been banned, in its development the implementation of interfaith marriages already has loopholes to deal with their marriages. Through smuggling or legal breaches in 4 ways, Requesting a court order, Marriages are carried out according to each religion, temporary submission to one of the rights of religion, and marrying abroad.The research method used is normative research. The approach used is the fact approach and the legal concept analysis approach. The data used are primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection is done by literature study. Then the collected data were analyzed qualitatively.Legal Breakthrough Against Interfaith Marriage Provisions concluded that interfaith marriage is prohibited both according to the law of each religion and the provisions of Indonesian state law. But in practice now, there are several ways that can be done to get around interfaith marriages in order to get marriage legalization, namely by breaking the law on the provisions of interfaith marriages.Keywords : Marriage , legal breakthrough, Different Religion Abstrak Marriage is a religious matter in which a relationship between two human beings, namely men and women who have grown up, has the desire to unite and promise in a sacred bond as husband and wife to form a happy family and multiply offspring. There is a meeting between the values shared by the community. One of the impacts of cross-cultural encounters causing a marriage, one of which is inter-religious marriage. Given that Indonesian society consists of various ethnicities, tribes and religions, interfaith marriage is nothing new. Even though it has been banned, in its development the implementation of interfaith marriages already has loopholes to deal with their marriages. Through smuggling or legal breaches in 4 ways, Requesting a court order, Marriages are carried out according to each religion, temporary submission to one of the rights of religion, and marrying abroad.The research method used is normative research. The approach used is the fact approach and the legal concept analysis approach. The data used are primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection is done by literature study. Then the collected data were analyzed qualitatively.Legal Breakthrough Against Interfaith Marriage Provisions concluded that interfaith marriage is prohibited both according to the law of each religion and the provisions of Indonesian state law. But in practice now, there are several ways that can be done to get around interfaith marriages in order to get marriage legalization, namely by breaking the law on the provisions of interfaith marriages.Keywords : Marriage , legal breakthrough, Different Religion